Coleridge's laws : a study of Coleridge in Malta - Hough, Barry; Davis, Howard (Open Book Publishers, 2010)
"Samuel Taylor Coleridge is best known as a great poet and literary theorist, but for a period of his life he held real political power, acting as Public Secretary to the British Civil Commissioner in Malta in 1805. Barry Hough and Howard Davis show how Coleridge's actions in this role differ markedly from the idealism he had advocated before taking office--shedding new light on Coleridge's sense of political and legal morality. Meticulously researched and including newly discovered archival materials, Coleridge's Laws provides detailed analysis of the laws and public notices drafted by Coleridge, together with the first published translations of them."--Publisher's description
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Political activity.; Coleridge, Samuel Taylor, -- 1772-1834.; Colonial administrators -- Malta.; Law -- Malta -- History.; Poets, English -- 19th century -- Biography.; Poets, English -- Homes and haunts -- Malta.; Critics -- Great Britain -- Biography.; Poètes anglais -- 19e siècle -- Biographies.; Britanniques -- Malte -- Histoire -- 19e siècle.; Poètes anglais -- Résidences et lieux familiers -- Malte.; Critiques -- Grande-Bretagne -- Biographies.; Administrateurs coloniaux -- Malte.; Droit -- Malte -- Histoire.; Biography and True Stories.; Biography: general.; Biography: literary.; Jurisprudence and general issues.; Law.; Legal history.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Colonial administrators.; Political participation.; Malta.; Malta; Romantic literature; Legal history; Colonialism; Maltese history; British imperial history; Nineteenth century; Romanticism; Political history; Colonial government; Electronic books.; collective biographies.; Biographies.; History.